Utilization of Unmanned Aerial Vehicle (UAV) for Topographic Survey Using Ground Control Points (GCP) from Geodetic GNSS - Nizamuddin Nizamuddin; Freddy Sapta Wirandha; Ardiansyah . (Graduate Program of Syiah Kuala University, 2023)
In connection with the development plan of the USK campus II area, it is necessary to map the area to support and complete the necessary data. Mapping with an Unmanned Aerial Vehicle (UAV) is a strategy or way for large-scale mapping with a faster and more efficient time. It can save time compared to using conventional survey methods. Ground Control Point (GCP) measurements are carried out with geodetic GNSS to improve the accuracy/correction of the geometry of the aerial portrait results. This research aims to provide preliminary information about the topographic conditions and current appearance of the USK campus II development location. The results of the aerial photo research with a spatial resolution of 5 cm/pixel show that most of the area looks green, which is a forest area. Some areas in the west and north, such as in the rectorate block, are C excavation mining areas. Based on contour data in the USK II area, the PON block's ground elevation is 66 to 301 meters, in the faculty block, 50 to 260 meters, and in the rectorate block, 90 to 188 meters.